THE RELATIONSHIP BETWEEN LEARNING OUTCOMES ENTREPRENEURSHIP AND LEARNING OUTCOMES VOCATIONAL AUTOMOTIVE INTEREST STUDENT WORK CLASS X IN SMK MUHAMMADIYAH KARANGMOJO - Al Hashmy Hardhiansyah; Suparmin Suparmin (Jurnal Taman Vokasi, 2016)
The study aimed to describe (1) correlation between automotive vocational learning with working interest; (2) correlation between entrepreneurship learning achievement with working interest of welding subject; and (3) correlation between automotive vocationallearning and entrepreneurship learning achievement with students’ working interest. This study was ex-post facto research. Data collecting methods were questionnaires and documentation. Data analyzing methods used descriptive analysis, first and second hypothesis testing used partial correlation and third hypothesis testing used double regression. This study shows that (1) there was a positive and significant correlation between automotive vocationallearning with learning achievement with the score of r obs = 0,308 with the significant score 0.015 < 0.05; (2) there was a positive and significant correlation between entrepreneurship  learning achievement  with working interest among with the score of r obs = 0,493 with the significant score 0.015 < 0.05; and (3) there was a positive and significant correlation between automotive vocationallearning and entrepreneurship  learning achievement  with working interest  with the significant score 0.000 < 0.05. The score of determinant coefficient (R2) 0.252, it means that automotive vocationallearning and entrepreneurship  learning achievement  gave a positive contribution 25.2% toward working interest, while 74.8 % was influenced by other factors that were not discussed in this study. The automotive vocationallearning gave contribution 12.08% toward students’ working interest and entrepreneurship learning achievement gave contribution 13.12% toward students’ working interest.